The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1590/s0100-40422000000100006
|View full text |Cite
|
Sign up to set email alerts
|

Sistema automático para determinação seqüencial de cianeto livre e total empregando eletrodo tubular íon-seletivo de membrana homogênea

Abstract: AUTOMATIC SYSTEM FOR SEQUENTIAL DETERMINATION OF FREE AND TOTAL CYANIDE USING HOMOGENEOUS MEMBRANE TUBULAR ION-SELECTIVE ELECTRODE.This study presents an automated system for potentiometric determination of free and total cyanide which employs a homogeneous membrane tubular ion-selective electrode. After the electrode is assembled, it is connected to a system composed of 3 three-way solenoid valves, sample line, carrier line, acid stream, and gas diffusion chamber. A Turbo Pascal ® computer program, developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
(17 reference statements)
0
1
0
2
Order By: Relevance
“…29 The development of homogenous membrane tubular ion-selective electrode for cyanide determination was investigated by Queiroz and co-workers. 30 Also a tubular ion selective electrode based on the ionophore nanoctin on PVC membrane is described for ammonium determination. 31 An example of macrocyclic compound used for anion recognition was described by Stradiotto and co-workers 16 These authors have developed novel acyclic ruthenium (II) bipyridyl complexes, shown in Figure 1, which were designed as receptor complexes and which were successfully applied as potentiometric sensors for chloride ions.…”
Section: Potentiometric Sensorsmentioning
confidence: 99%
“…29 The development of homogenous membrane tubular ion-selective electrode for cyanide determination was investigated by Queiroz and co-workers. 30 Also a tubular ion selective electrode based on the ionophore nanoctin on PVC membrane is described for ammonium determination. 31 An example of macrocyclic compound used for anion recognition was described by Stradiotto and co-workers 16 These authors have developed novel acyclic ruthenium (II) bipyridyl complexes, shown in Figure 1, which were designed as receptor complexes and which were successfully applied as potentiometric sensors for chloride ions.…”
Section: Potentiometric Sensorsmentioning
confidence: 99%
“…Outra característica indesejável destes contaminantes é o fato de que, no processo de cloração da água potável, a sua reação com cloro produz clorofenóis e polifenóis que são carcinogênicos, além de que os compostos fenólicos causam diversos problemas ambientais (BASTOS, 1995 Os POAs dividem-se em sistemas homogêneos, que promovem a reação entre um catalisador e o resíduo orgânico, ou apenas o resíduo em uma única fase, e sistemas heterogêneos, que envolvem catalisador, quelantes na fase sólida e os resíduos, formando duas ou mais fases, sendo que em ambos os sistemas promove-se a geração dos radicais hidroxila, com ou sem o uso da radiação ultravioleta (NOGUEIRA et. al., 2007 (MARIN et al, 2000). Nas instituições de ensino e pesquisa o cianeto é utilizado como reagente em alguns procedimentos analíticos, notadamente como padrões em desenvolvimento de métodos objetivando a determinação da espécie química (MARIN et al, 2000;FIGUEROLA et al, 1988).…”
Section: Introductionunclassified
“…al., 2007 (MARIN et al, 2000). Nas instituições de ensino e pesquisa o cianeto é utilizado como reagente em alguns procedimentos analíticos, notadamente como padrões em desenvolvimento de métodos objetivando a determinação da espécie química (MARIN et al, 2000;FIGUEROLA et al, 1988).…”
Section: Introductionunclassified